Penerapan Model Numbered Head Together untuk Meningkatkan Hasil Belajar Aqidah Akhlak MTS Swasta Yaspen Muslim Pematang Tengah - Anggara, Ari; Fazri, Hasnatul; Nasution, Usmansyah (LP3M STAI Ibnurusyd, 2024)
This research was motivated by the low learning outcomes of class VII-4 students at MTs Private Yaspen Muslim, Central Pematang in the subject of moral aqidah. The aim of this research is to find out whether the numbered head together model can improve students' academic achievement in the aqidah akhlak material about the second pillar of faith at MTs Private Yaspen Muslim Pematang Tengah for the 2023/2024 academic year. By using this model, teachers can easily stimulate student activity by setting tasks and questions for students to work on together in small groups. Teachers can easily monitor student activities, so they know the level of difficulties and problems students face, and teachers can find solutions. The results of this research show that the numbered head together learning model can improve student learning outcomes. This can be seen from the results of data analysis from the previous cycle with an average of 71.3 and completeness representation of 41%. Cycle I had an average of 77.4 and a completion rate of 76%, increasing to an average of 85.40 and a completion rate of 97% in cycle II. It can be concluded that the application of the numbered head together model can improve the learning outcomes of moral aqidah material regarding the second pillars of faith for class VII-4 MTs Private Yaspen Muslim Central Pematang academic year 2023/2024. The impact of this research is very important, especially for a moral aqidah educator to improve student learning outcomes in the learning process.